The checklist of longhorn beetles (Coleoptera: Cerambycidae) from India - Kariyanna, B.; Mohan, M.; Gupta, Rajeev; Vitali, Francesco (Zootaxa, 2017)
A checklist of longhorn beetles (Coleoptera: Cerambycidae) within the present geographical frontier of Indian subcontinent up to 2016 is provided. As per the current checklist prepared, there are 1536 species, classified under 440 genera, 72 tribes, and seven subfamilies of Cerambycidae (Parandrinae is not present in India). The report is accounted for 4.2 per cent of species, 7.94 per cent of genera and 28.24 per cent of tribes from India as compared to global record. For each species, accepted nomenclature followed by all relevant works reporting systematics, distribution and ecology of Indian longhorn beetles is provided along with synonyms, type locality and distribution within and outside India.